Taiwan’s development of neoliberalism - Siti Hilya Nabila (Journal of Economic, Business & Accounting Research, 2023)
This article analyzes the adoption of neoliberalism in Taiwan and its impact on financial, labor, and industrial policies. Taiwan adopted neoliberalism in the late 1970s, facing challenges in maintaining autonomy against global pressures and domestic business interests. The state-controlled market underwent a significant transformation because of the sacrifices made for various stakeholders. Taiwan's strong economic growth has been recognized globally, making it an example for other developing countries to implement neoliberal policies. This article focuses on the period after the 2008 global financial crisis, in which Taiwan implemented monetary and fiscal policies to stabilize the financial system and generate domestic demand. While supporting corporate financing and facilitating personal relationships with banks, the government aims to restore financial stability. The Taiwanese state has consistently pursued the values of neoliberalism while maintaining balance with societal-oriented policies. The government's approach to this problem has evolved, demonstrating efforts to overcome the side effects of neoliberal policies. Ultimately, Taiwan's economic development reflects the complex play of neoliberalism and its impact on various sectors in the country.